Blood Culture Contamination in a Community Hospital- less than 2% is achievable. (28th October 2021) - Bedi, R; Atkinson, J
Abstract: Introduction/Objective: Blood cultures are commonly obtained to evaluate the presence of bacteria or fungal infection in a patient's bloodstream. The presence of living microorganisms circulating in the bloodstream is of substantial prognostic and diagnostic importance. A positive blood culture indicates a reason for the patient's illness and provides the etiological agent for antimicrobial therapy. Collection of blood culture is an exact process that requires time, the proper order of draw, and following of correct protocol. The busy Emergency department that requires multiple demands for nurse's time, turnover of staff, rushing from one task to another can result in the improper collection and false-positive blood cultures. The national benchmark is set at 3% by the American Society of Clinical Microbiology (ASM) and The Clinical and Laboratory Standard Institute (CLSI). False-positive blood culture results in increased length of stay and unnecessary antimicrobial therapy, resulting in an increased cost burden to the hospital of about $5000 per patient. Methods/Case Report: At our 150-bed community hospital, 26 beds Emergency Department, we have come a long way in reduction of our blood culture contamination rates from upwards of 4% to less than 2%, far lower than the national benchmark. Results (if a Case Study enter NA): NA Conclusion: There are multiple devices available from various manufacturers claiming to reduce blood culture contamination. These devices do reduce blood culture (BC) contamination but at an added cost of the device. The rate of BC can be reduced and less than 3% is achievable by materials available in the laboratory. We have achieved this by providing training to every new staff by demonstration and direct observation, providing everything required for collection in a kit, using proper technique, the inclusion of diversion method that involves the aseptic collection of a clear tube before collecting blood cultures, and following up monthly on any false positive blood cultures.